Scientific Reading Based Project (SRBP) in Elementary IPAS Learning: A Theoretical and Empirical Review for Sustainable Education Development - Hastuti, Yani Dwi; Suryandari, Kartika Chrysti; Roemintoyo, Roemintoyo (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
Elementary IPAS learning requires innovative instructional models to develop students’ creative thinking, scientific literacy, and readiness for technology-based sustainable education. This study aims to examine the implementation of the Scientific Reading-Based Project (SRBP) model in elementary IPAS learning from both theoretical and empirical perspectives. This study employs a Systematic Literature Review (SLR) of reputable national and international publications within the last five years (2020–2025), supported by an analysis of empirical research findings related to SRBP implementation. The findings show that SRBP effectively enhances students’ creative thinking skills, scientific literacy, and learning motivation through the integration of digital scientific reading and technology-based learning resources. In addition, SRBP promotes contextual project-based learning oriented toward real-world problem solving and strengthens students’ engagement and collaboration. Therefore, SRBP can be considered an innovative instructional model that supports the development of sustainable and technology-based IPAS learning in elementary schools.